2020
DOI: 10.1002/adtp.202000146
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation of Recombinant Human Deoxyribonuclease I Provides a Long‐Acting Version of the Mucolytic for Patients with Cystic Fibrosis

Abstract: Inhalation of recombinant human deoxyribonuclease I (rhDNase) is a gold-standard therapy in the management of cystic fibrosis (CF). Yet, the rapid elimination of the mucolytic from the lungs requires its daily administration and rhDNase contributes to the high therapy burden of patients. Here, a long-acting version of rhDNase that is delivered once weekly instead of once daily is presented. Conjugation of rhDNase to a polyethylene glycol (PEG) chain sustains its presence and mucolytic activity within murine lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…Macrophage uptake was also reported for PEG40-Fab', PEG30-rhDNase, and PEGs of up to 40 kDa after pulmonary delivery [19,25,27,33]. While no quantitative data were collected in the present work, another study from our laboratory demonstrated that the uptake of PEGylated anti-IL13 Fab' by alveolar macrophages was slightly less efficient than its non-PEGylated counterpart in mice [19].…”
Section: Lung Local Distribution Of Native and Pegylated Rhdnasesupporting
confidence: 63%
See 3 more Smart Citations
“…Macrophage uptake was also reported for PEG40-Fab', PEG30-rhDNase, and PEGs of up to 40 kDa after pulmonary delivery [19,25,27,33]. While no quantitative data were collected in the present work, another study from our laboratory demonstrated that the uptake of PEGylated anti-IL13 Fab' by alveolar macrophages was slightly less efficient than its non-PEGylated counterpart in mice [19].…”
Section: Lung Local Distribution Of Native and Pegylated Rhdnasesupporting
confidence: 63%
“…Previously published works have shown that conjugation of proteins to PEGs of MWs ≥ 20 kDa has a high potential for increasing their residence time in the lungs [13,[18][19][20]27]. More recently, Guichard et al demonstrated the prolonged residence time of 30 and 40 kDa PEG conjugates of rhDNase in the lungs of mice for more than 15 days compared to merely 24 h for the unconjugated rhDNase [25]. They also demonstrated the improved therapeutic efficacy of PEG30-rhDNase in β-ENaC mice, a model of the CF lung disease, as well as its safety after single and repeated administration to healthy mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19] Conjugation of PEG to recombinant human deoxyribonuclease I (rhDNase) resulted in an impressive extension of its residence time (≥15 days) in the murine lungs. [20] Moreover, one single dose of PEGylated rhDNase was as effective as 1 daily dose of unconjugated rhDNase during 5 days in decreasing the DNA content in the lungs of β-ENaC mice, a model of the cystic fibrosis lung disease. The lack of marketed PEGylated proteins for pulmonary delivery reflects the paucity of approved proteins for inhalation in the first place.…”
Section: Prolongation Of Serum Half-life and Residence Time In The Lungsmentioning
confidence: 95%